TO BE A TREND SPONGE: EDITORS AND INTUITIVE DEMAND FORECASTING IN BIG PUBLISHING HOUSES - Miguel, Paula; Saferstein, Ezequiel (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
This paper analyses the practices of publishers who work in the global conglomerates in Argentina. Their careers and professional profiles, the ways they deal with the editorial production, marketing and management, are shared elements. Among these shared elements is established the requirement to publish and sell books (a common feature of large publishing houses), the configuration of a trends publisher and what we can analytically think as the construction of an ethos that combines elements that make the recognition of a "good editor", taking part in their professional careers that intertwines with their life experiences and their sense of one’s place. This ethos shows tensions between "inspirational" or creative "intuitions" and a new business logic that looks forward to transparent the process in which production of best-sellers take part, and they combine into what editors identified as "business sense", which involves adaptations and regulations at different levels of professional and personal practice.This paper is based on the results of ongoing qualitative researches, which seek to analyze different ways of production, circulation and consumption of "creative" goods, considering that in such circuits we can find implicit notions of subjectivity.